Prepositioning of driving simulator motion systems. (2015) - Hansson, P.; Stenbeck, A.; Kusachov, A.; Bruzelius, F.; Augusto, B.
Motion base driving simulators have limited space in which to recreate the motions of the simulated road vehicle. Conventional motion cueing algorithms strive to centre the cabin in the simulator motion envelope to accommodate accelerations in a worst case scenario while respecting the physical boundaries. Using information about the road ahead one can preposition the cabin to an off-centre point, virtually increasing the available space so that larger motions are made possible. The prepositioning algorithm presented here was developed as an addition to a classical motion cueing algorithm and makes use of road data and vehicle speed to adjust the simulator displacement. Simulations show that the amount of acceleration presented by an x, y-sled system can, with prepositioning, be increased by up to 25% in longitudinal and 53% in lateral direction for an example road. A comparative study including 12 test subjects indicates that the perceived realism is rated higher with prepositioning.